2018
DOI: 10.1002/ece3.4623
|View full text |Cite
|
Sign up to set email alerts
|

Within‐species trade‐offs in plant‐stimulated soil enzyme activity and growth, flowering, and seed size

Abstract: Soil microbial communities affect species demographic rates of plants. In turn, plants influence the composition and function of the soil microbiome, potentially resulting in beneficial feedbacks that alter their fitness and establishment. For example, differences in the ability to stimulate soil enzyme activity among plant lineages may affect plant growth and reproduction. We used a common garden study to test differences in plant‐stimulated soil enzyme activity between lineages of the same species across dev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 40 publications
0
4
0
Order By: Relevance
“…Non-AMF rhizosphere microbial communities and their influence on plant growth can change over generations due to local natural selection processes (Gomola, McKay, Wallenstein, Wagg, & O'Brien, 2018;Lau & Lennon, 2011;Wagg et al, 2015). Therefore, inoculating plants with non-AMF microbial communities collected from plant monocultures should be more detrimental to plant growth if monocultures accumulate a greater abundance of pathogens.…”
Section: Non-amf Microbial-community Effects On Diversity-selected mentioning
confidence: 99%
“…Non-AMF rhizosphere microbial communities and their influence on plant growth can change over generations due to local natural selection processes (Gomola, McKay, Wallenstein, Wagg, & O'Brien, 2018;Lau & Lennon, 2011;Wagg et al, 2015). Therefore, inoculating plants with non-AMF microbial communities collected from plant monocultures should be more detrimental to plant growth if monocultures accumulate a greater abundance of pathogens.…”
Section: Non-amf Microbial-community Effects On Diversity-selected mentioning
confidence: 99%
“…Plant root activity, through root exudation, rhizodeposition and nutrient uptake, shifts the energetic and nutrient balance of rhizosphere soils (Hinsinger et al, 2009;Bell et al, 2015). Therefore, plant phenotypic variation in resource acquisition and use may offer a framework to understand plant species and genotype variation in rhizosphere effects (Zancarini et al, 2013;Gomola et al, 2018). Plants with high relative growth rate (RGR) frequently have higher rates of root exudation, and support increased growth and turnover of microbial populations in the rhizosphere (Blagodatskaya et al, 2014;Ka stovsk a et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…The outcome of this study revealed that the contents of alkaline protease, alkaline phosphatase, catalase, and sucrase increased with the increase in the growth stages (Table 3). This further indicated that industrial hemp could degrade macromolecules into small molecules through soil enzymes in a rhizosphere environment to support its own growth, thus regulating the cycle of soil carbon, nitrogen, and phosphorus [34]. Earlier research has demonstrated a positive association of the activities of soil sucrase and soil alkaline phosphatase with SOC and microbial biomass, indicating that these components contain substrates that induce the synthesis of these enzymes [35].…”
Section: Responses Of Soil Nutrients and Enzyme Activities To Differe...mentioning
confidence: 94%